Early outcome after off-pump coronary artery bypass grafting: effect on mortality and stroke - Reber,Delawer (2008)
OBJECTIVE: One of the major and devastating complications of the coronary artery bypass grafting (CABG) is the stroke. Avoiding cardiopulmonary bypass (CPB) may reduce this neurological complication. In the past years there was an increased interest in the off-pump coronary artery grafting (OPCAB). The benefit of this method of revascularization in term of stroke and mortality is controversially discussed. METHODS: A retrospective analysis of collected data from 252 patients were operated without cardiopulmonary bypass out of 1516 CABG procedures from January 2004 through May 2006. The mean age of the patient population was 70±11years, within a range of 27-88 years. Forty-eight (19%) patients were older than 80 years and there were 172 (69%) males. Mean graft per patient was 1.78±0.79. The internal mammary artery (IMA) graft was used in 95% of the patients. For eight (3.17%) patients this was the second procedure. RESULTS: Hospital mortality was 3.17%; Mean EuroSCORE in these patients was 10.36±6.67. No neurological complications occurred, six (2.38%) patients had temporary psycho syndrome. Postoperative myocardial infarction occurred in three (1.19%) patients. Two patients required rethoracotomy as a result of bleeding. Thirty-eight (15%) patients needed postoperative therapy for atrial fibrillation. CONCLUSION: CABG with OPCAB technique has the benefit of low mortality and morbidity in terms of stroke. The advantages of this technique depends on the patient's general condition at the time of the operation, the sufficiency of pump function and coronary morphology, as well as on the surgeon's experience.